Faktor-Faktor yang Berhubungan dengan Tingkat Kecemasan pada Tenaga Kesehatan saat Pandemi COVID-19 (Studi di RSUD Dr. Moewardi Surakarta) - Rani Wijayanti; Retno Hestiningsih; Sri Yuliawati; Nissa Kusariana (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: When the COVID-19 pandemic occurred, healthcare workers were under pressure, especially those who had direct contact with confirmed cases of COVID-19 due to the high risk of infection. These factors can lead to increased psychological problems in health workers such as anxiety. Therefore, it is necessary to analyze the factors that can cause anxiety during the COVID-19 pandemic. In this research was conducted at RSUD Dr. Moewardi Surakarta.Methods: This study used a cross-sectional study design. The sample size in this study was 103 respondents. The sampling technique used was purposive sampling.Result: The results of this study indicate that the factors associated with the level of anxiety are age (p-value = 0.037), gender (p-value = 0.003), and years of service (p-value = 0.023). Factor that is not related to the level of anxiety is marital status (p-value = 0.830).Conclusion : It can be concluded that age, gender, years of service are factors related to the level of anxiety in health workers at RSUD Dr. Moewardi Surakarta.